A study of the historiography of philosophy in French-speaking philosophy - Yosypenko, Serhii (Sententiae, 2022)
One of the traditional subjects of discussion among historians of philosophy is the question of the status of the history of philosophy as well as a discipline, as well as the tasks, possibilities, and limitations of some approaches and genres of the historiography of philosophy. The article focuses on the analysis of the contribution to these discussions of studies in the historiography of philosophy, which began in Francophone philosophy in the 1970s with the publication of the studies of L. Braun and M. Gueroult, in particular, the answers to the mentioned questions, proposed within the framework of these studies. The starting point of the article is the historical scheme of the attitude of philosophers to the past of philosophy, proposed by Y. Lafrance, which makes it possible to determine the place of the history of philosophy as a discipline in philosophical activity and to study the historiography of philosophy as an element of such activity. In this article, three research projects of the historiography of philosophy were analyzed – the «history of the history of philosophy» by L. Braun, the studies in the doxography by A. Laks and M. Frede, the social history of the historiography of philosophy by C. König-Pralong. Based on the analysis of the mentioned projects, the article support the conclusion that the history of philosophy cannot be considered either only as a historical or only as a philosophical discipline, and also that a historian of philosophy cannot investigate a subject without simultaneously constructing it on the basis of historical data, which always remain outside the historiographic construction.